2018
DOI: 10.1073/pnas.1719335115
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic boundaries constrain microbial diversity gradients in the South Pacific Ocean

Abstract: Marine microbes along with microeukaryotes are key regulators of oceanic biogeochemical pathways. Here we present a high-resolution (every 0.5° of latitude) dataset describing microbial pro- and eukaryotic richness in the surface and just below the thermocline along a 7,000-km transect from 66°S at the Antarctic ice edge to the equator in the South Pacific Ocean. The transect, conducted in austral winter, covered key oceanographic features including crossing of the polar front (PF), the subtropical front (STF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
90
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 65 publications
19
90
3
Order By: Relevance
“…This differs from previous studies of host-associated marine microbial communities, where alpha diversity significantly differed between collection sites (Luter et al, 2015;Pantos et al, 2015). Similarly, pelagic microbial diversity has been shown to change across major oceanographic boundaries (Raes et al, 2018). Thus, our results suggest that marine biogeographic boundaries may affect the diversity of intertidal gastropod-associated microbial communities differently from that of other groups.…”
Section: Site Specificity In the Marine Gastropod Microbiomecontrasting
confidence: 99%
See 2 more Smart Citations
“…This differs from previous studies of host-associated marine microbial communities, where alpha diversity significantly differed between collection sites (Luter et al, 2015;Pantos et al, 2015). Similarly, pelagic microbial diversity has been shown to change across major oceanographic boundaries (Raes et al, 2018). Thus, our results suggest that marine biogeographic boundaries may affect the diversity of intertidal gastropod-associated microbial communities differently from that of other groups.…”
Section: Site Specificity In the Marine Gastropod Microbiomecontrasting
confidence: 99%
“…Little is known at present about the role of marine biogeographic boundaries in structuring spatial patterns of microbial species richness and composition, but a recent study suggests that richness of free‐living bacterial, archaeal and microeukaryotic taxa can change across oceanographic boundaries (Raes et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recent advances in process-based macroecology (Cabral et al, 2017;Connolly et al, 2017) and trait-based approaches (Kiørboe et al, 2018) are making advances in terms of dynamic prediction of macroecological patterns, including across scales. Isotopic methods are helping bridge the trophic gaps at larger spatial and temporal scales (Hobson et al, 2010;Quillfeldt et al, 2010) and new metagenomic methods are being used to generate new ecosystem scale maps of active processes and biodiversity (Raes et al, 2018). As we outline above, nested network approaches are also helping to link understanding of interactions and connectivity across processes, space, and time (Pilosof et al, 2017).…”
Section: Gaps In Fundamental Ecological Understandingmentioning
confidence: 99%
“…Recent metagenomics and metatranscriptomics work from the Tara Oceans Project suggested that, in polar regions, the effects of ocean warming on bacterial communities will be stronger on a community (composition) level than on a gene (regulatory) level 6 . On a basin scale, Raes, Bodrossy 7 showed that permanent oceanographic frontal systems can have a signi cant in uence on both the alpha-and beta-diversity of prokaryotes and microbial eukaryotes. In addition, their data supported a strong positive link between productivity and microbial diversity.…”
Section: Introductionmentioning
confidence: 99%